Housing and credit misalignments in a two-market disequilibrium framework - Jaunius Karmelaviécius; Ieva Mikaliunaitçe-Jouvanceau; Austçeja Petrokaitçe (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
During the COVID-19 pandemic, house prices and mortgage credit rose at a longunseen pace. It is unclear, however, whether such increases are warranted by the underlying market and macroeconomic fundamentals. This paper offers a new structural two-market disequilibrium model that can be estimated using full-information methods and applied to analyse housing and credit dynamics. Dealing with econometric specification u ncertainty, w e e stimate a l arge e nsemble o f t he two-market disequilibrium model specifications f or Lithuanian m onthly d ata. U sing t he model estimates, we identify the historical drivers of Lithuania's housing and credit demand and supply, as well as price and market quantity variables. The paper provides a novel approach in the financial s tability literature t o j ointly m easure h ouse price overvaluation and mortgage credit flow g aps. We find that, by mid-2021, Lithuania was experiencing a heating-up in housing and mortgage credit markets, with home prices overvalued by around 16% and the volume of mortgage credit flow being 20% above its fundamentals.
Keywords: C34; D50; E44; E51; G21; 330; disequilibrium; fundamentals; misalignments; house prices; mortgage credit; early warning indicators